Factors Influencing Brain Drain among Nurses of Selected Hospital of Kathmandu - Sandha, Usha; Shrestha, Moonu (Purbanchal University Health Journal, 2025)
Introduction: A Research study was conducted on factors influencing brain drain among nurses of selected hospitals of Kathmandu. Brain drain is the mass emigration of individuals with technical skills or knowledge, generally due to a lack of prospects, political instability, conflict or health issues, and other risk factors. Brain drain is also called “The human capital flight”. Objective: This study was conducted to identify the factors contributing to brain drain among nurses of selected hospital of Kathmandu. Method: A cross-sectional descriptive study was conducted among 72 nurses of Civil Service Hospital using a non-probability convenient sampling technique. Data collection was done by the researcher herself using a self-administered questionnaire. Validity and reliability of the instrument and ethical consideration were maintained. Data were analyzed with the help of the SPSS 26th version and were analyzed with descriptive and inferential statistics like frequency, percentage, and chi-square test. Result: The findings of the study showed that out of 72 nurses, 64 (88.9%) of nurses had brain drain intention. Here, 9 in 10 respondents agreed on personal factors and environmental factors followed by safety and security and social factors in push factors as major factors for brain drain. And, 9 in 10 respondents agreed on personal factors followed by economic factors and social factors in pull factors. In this study, there was no association between the socio-demographic variables and push and pull factors except in monthly income in Nepal and environmental factors of push factors. There was a significant association between monthly income in Nepal and environmental factors of push factors. The p-value is 0.030 (p-value <0.05). Conclusion: From the result of this study, it is concluded that personal and environmental factors are the major factors causing the brain drain of nurses so concerned authorities should focus on exploring more factors so that timely intervention can be done.